Islam Penginyongan: Orientation of Local Wisdom towards Ebeg Tradition in Islamic Studies and Local Culture - ., Nawawi (Journal of Ecohumanism, 2024)
Javanese culture has become the center of study for many Indonesians, due to its historical dominance in the fields of politics, economics, culture, and its status as a major ethnic group in the archipelago. Throughout its history, Javanese culture has gradually absorbed various elements and influences and has been influenced by various interactions for more than a millennium from foreign cultures and civilizations. Islamic values, harmony between movement, music and lyrics in art ok can represent spiritual concepts in Javanese beliefs. This ritual becomes a channel for the expression of spirituality, connecting humans with higher dimensions and honoring the presence of spiritual forces. The method in this research is qualitative. The results of this research are: in art ok, process machine is a powerful reflection of humanity’s greed and lust for the world. This is a moral message and reminder about the importance of maintaining balance, caring for spiritual values, and avoiding excessive attachment to material things that can disrupt one’s relationship with God. Through procession machine will provide a moral message about the importance of controlling oneself and avoiding negative behavior that can harm oneself and others. Just as this procession illustrates the effects of uncontrolled lust, so too can behavior such as gambling and other vices have a negative impact on a person’s life and social relationships. On the other hand, Art ok encourage responsibility to maintain good relationships with law. In all, procession machine for someone is a form of expression of gratitude, appreciation, and happiness to law.